Treatment of recurrent ovarian cancer: Survey of practice among Thai gynecologic oncologists - T. Manchana (2020)
© Journal of The Medical Association of Thailand Objective: To survey the practice among Thai gynecologic oncologists in the treatment of recurrent epithelial ovarian cancer. Materials and Methods: This study was a part of the Thai Gynecologic Cancer Society (TGCS) national survey about the practice among Thai gynecologic oncologists. Their responses to 21 questions about the treatment of epithelial ovarian cancer were analysed. Results: Among 258 gynecologic oncologists who met the inclusion criteria, 170 responded to the questionnaires (65.9%). Almost half of Thai gynecologic oncologists who participated in this survey reported that they performed surgery after recurrence of ovarian cancer, but in only 10% of their patients. Combination of platinum and paclitaxel was the most preferable regimen (90%) in recurrent platinum-sensitive epithelial ovarian cancer. The most common second-line chemotherapeutic regimen for recurrent platinum-resistant or platinum-refractory epithelial ovarian cancer patients was gemcitabine (53.5%) followed by pegylated liposomal doxorubicin (42.4%) and single paclitaxel (4.1%). Best supportive care was given more frequently after a failure from 2 or more regimens. If the patients did not respond to more than 3 chemotherapy regimens, 70% of the responders offered the best supportive care to their patients. The responders prescribed targeted therapy with the median number of 5% for their patients. Conclusion: Chemotherapy was the most common treatment for recurrent ovarian cancer. Reimbursement by the Thai Universal Health insurance limited using various chemotherapeutic agents including targeted therapy. Best supportive care was wildly chosen as the treatment option in recurrent platinum-resistant epithelial ovarian cancer patients who failed more than 3 chemotherapy regimens.